2016
DOI: 10.1021/acs.jafc.6b04041
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Derived from Soy and Lupin Protein as Dipeptidyl-Peptidase IV Inhibitors: In Vitro Biochemical Screening and in Silico Molecular Modeling Study

Abstract: Dipeptidyl peptidase IV (DPP-IV) is a new molecular target correlated with the development of type 2 diabetes. Literature describes the identification of some inhibitory peptides from the hydrolysis of different food proteins. This article reports a study on six peptides from soybean and lupin proteins, i.e., Soy 1 (IAVPTGVA), Soy 2 (YVVNPDNDEN), Soy 3 (YVVNPDNNEN), Lup 1 (LTFPGSAED), Lup 2 (LILPKHSDAD), and Lup 3 (GQEQSHQDEGVIVR), which were screened for their capacity to inhibit the activity of DPP-IV, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 41 publications
(108 reference statements)
2
86
1
1
Order By: Relevance
“…For instance, aromatic residues such as phenylalanine were found at the Ct end of peptides VVAEQAGEQGFE and HKNKNPF from F3. Proline was present at favorable positions of the N-terminal end of peptides VVNPDNNEN, EEPQQPQQ, QEPQESQQ, SQRPQDRHQ, and PETMQQQQQQ from F1 and SSPDIYNPQAGSVT from F3, although proline was not flanked by leucine, valine, phenylalanine, alanine, and glycine, in contrast with previous studies [ 35 , 36 ]. In addition, most of the peptides from F3 contained from four to six hydrophobic amino acid residues.…”
Section: Resultscontrasting
confidence: 95%
“…For instance, aromatic residues such as phenylalanine were found at the Ct end of peptides VVAEQAGEQGFE and HKNKNPF from F3. Proline was present at favorable positions of the N-terminal end of peptides VVNPDNNEN, EEPQQPQQ, QEPQESQQ, SQRPQDRHQ, and PETMQQQQQQ from F1 and SSPDIYNPQAGSVT from F3, although proline was not flanked by leucine, valine, phenylalanine, alanine, and glycine, in contrast with previous studies [ 35 , 36 ]. In addition, most of the peptides from F3 contained from four to six hydrophobic amino acid residues.…”
Section: Resultscontrasting
confidence: 95%
“…Further in vitro and in silico studies demonstrated that peptide IAVPTGVA was an efficient inhibitor of dipeptidyl peptidase IV (DPP-IV), a serine exopeptidase. DPP-IV is responsible for the hydrolysis of glucagon-like peptide and glucose-dependent insulinotropic polypeptide which are critical for maintaining glucose homeostasis [ 52 ]. Although the peptides YVVNPDNDEN and YVVNPDNNEN had similar hypocholesterolemic activity as IAVPTGVA, they were ineffective at inhibiting DPP-IV due to their longer peptide sequence and lack of Pro as the fourth N-terminal residue [ 52 ].…”
Section: Soy Bioactive Peptides and Their Propertiesmentioning
confidence: 99%
“…Nevertheless, the peptides are complex and the use of a purification step following hydrolysis is common [ 7 , 8 , 9 ]. Alternatively, synthetic production of peptides [ 10 , 11 ] can be used to obtain specific peptides and study their physiological action.…”
Section: Diversity Of Bioactive Peptidesmentioning
confidence: 99%